An Examination of the NGO Sector Competitive Environment in Kenya - Arasa, Robert; Kioko, Mary (IJSR, 2014)
The nonprofit sector firms tend to focus more on the internal facets giving little attention to the ever dynamic external business environment. There is notable growth in the NGO sector in terms of numbers of firms seeking donor support as a source to actualizing their intentions and initiatives. Increased number of NGOs and declining funding implies increased competition for the scarce donor funding. This study examines the NGO competitive environment in Kenya with a focus on the heath sector, HIV/AIDs subsector. A descriptive survey design was employed confining the study to Nairobi which houses the largest number of NGOs in Kenya (35%). From a study population of 313 a sample size of 10% was picked. Stratified sampling procedure was employed to ensure representativeness in the sample while a purposive approach was utilized to pick target respondents. Descriptive analysis technique was used to analyze data. Study findings reveal that indeed there exists competition within the NGO sector, emanating not only from within the NGO sector but also from private sector organizations, government, academic institutions, faith-based institutions and research institutions. However, this competition cannot yet be categorized as intense. NGOs seem to be getting serious competition from academic institutions and least competition from faith-based institutions. The study recommends that NGOs should continuously scan, analyze and interpret forces shaping their competitive environment for purposes of appropriate realignment, survival and success.
Keywords: NGOs; Competition; Environment; Health sector; Donor funding; Kenya